Green Knowledge Sharing, Stakeholder Pressure, Absorptive Capacity, and Green Innovation: Evidence from Chinese Manufacturing Firms. (5th January 2020) - Song, Moxi; Yang, Morgan X.; Zeng, Kevin J.; Feng, Wenting
Abstract: A central issue faced by many Chinese manufacturing firms is how to absorb and utilize green knowledge shared among supply chain members for superior green innovation. Invoking the indirect research stream of organizational learning theory, we develop a moderated mediation model in which absorptive capacity mediates the interactive effects of green knowledge sharing and stakeholder pressure on green innovation. Our hypotheses were tested using a sample of 247 Chinese manufacturing firms. The results from multiple regression and bootstrapping tests reveal that absorptive capacity fully mediates the link between green knowledge sharing and green innovation, and the mediation effect is positively contingent upon stakeholder pressure. These findings provide managerial implications for Chinese manufacturing firms, recommending that these firms effectively develop their absorptive capacities and closely monitor stakeholder pressure to realize the green innovation benefits of green knowledge sharing.